Peranan faktor ekstralinguistik dalam pengajaran bahasa Melayu untuk penutur asing - Yong, Chyn Chye; Subramaniam, Vijayaletchumy; Chan, Tze Haw (Penerbit Universiti Pendidikan Sultan Idris, 2013)
This research is to examine the role of extralinguistic factors in teaching the Malay language as a foreign language at private institute of higher learning. The process in building an effective method of BM studies is limited by the dearth of evaluation efforts that focus on the teaching of Malay language as a foreign language, especially for the foreigners are studying in private higher education institutions. First and foremost, this research involved literature review, survey and observation in the classroom. The sample included 114 international students from 21 countries during Trimester 2 and 3, 2010/2011. The Sociaeducational Model by Gardner has been applied in this research. All the participants in the study’s sample had followed Bahasa Kebangsaan B subject for 14 weeks at one of the private universities in Malaysia. The results showed that the foreign speakers agreed that the process mastering of Malay language is motivated by extralinguistic factors, especially the integration factor. This research is important to uphold the Malay language as an international language in conjunction with the government’s intention to make Malaysia a regional hub for higher education.